1980
DOI: 10.1111/j.1600-0404.1980.tb03011.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of theophylline on the outcome of acute cerebral infarction

Abstract: In patients with acute ischemic stroke, dramatic but often transient improvements have been noticed after theophylline injections. Whether better results could be obtained by continuous infusion of the drug was evaluated in a double-blind study. Out of 46 patients with a mean age of 75 years, 22 got theophylline as aminophylline (bolus dose of 230 mg followed by 0.5 mg/kg/h) and 24 placebo during 3 days. The groups were comparable in all aspects at the outset of the trial. Serum theophylline concentrations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…For the placebo group one trial used physiological saline (Geismar 1976) and the other used 5.5% glucose (Britton 1980). Aminophylline was administered as either a 200 mg intravenous bolus dose (10 ml 2% solution in saline) infused over two minutes followed by 10 ml at three hours and 10 ml at six hours (Geismar 1976), or by intravenous loading dose of 230 mg followed by continuous intravenous infusion (0.5 mg/kg/h in 5.5% glucose) for 72 hours (Britton 1980). One trial reported change in neurological impairment using a locally developed scoring system (Geismar 1976); this trial also reported the Rankin score at three weeks.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…For the placebo group one trial used physiological saline (Geismar 1976) and the other used 5.5% glucose (Britton 1980). Aminophylline was administered as either a 200 mg intravenous bolus dose (10 ml 2% solution in saline) infused over two minutes followed by 10 ml at three hours and 10 ml at six hours (Geismar 1976), or by intravenous loading dose of 230 mg followed by continuous intravenous infusion (0.5 mg/kg/h in 5.5% glucose) for 72 hours (Britton 1980). One trial reported change in neurological impairment using a locally developed scoring system (Geismar 1976); this trial also reported the Rankin score at three weeks.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…One trial reported change in neurological impairment using a locally developed scoring system (Geismar 1976); this trial also reported the Rankin score at three weeks. The other trial reported changes in functional capacity, based on the patients ability to walk (Britton 1980). None of the trials reported quality of life.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…However, two small trials have provided little indication of any long-term benefits from aminophylline infusion during the acute stages. 87,88 Blood pressure augmentation with plasma expanders and inotropic agents is now an established part of the management of focal cerebral ischaemia following subarachnoid haemorrhage, and experimental results suggest that it has considerable promise as a therapeutic intervention in acute Vascular Medicine 1999; 4: 149-163 stroke. 89,90 As yet there are few reliable clinical studies on the use of inotropic or vasopressor drugs in stroke, but haemodilution using volume expanders alone, with or without venesection, has been quite widely evaluated, both experimentally and clinically.…”
Section: Other Means Of Improving Blood Flowmentioning
confidence: 99%